Sense of Purpose in Life Predicts University Performance and Attrition - Jacob E Alderson; Nathan A Lewis; Patrick L Hill; Nicholas A Turiano (Student Success)
Individual differences are important predictors of academic success. A sense of purpose in life is gaining increasing attention as a key individual difference factor to foster in university students. The current study examined whether a sense of purpose in life, a dispositional tendency to pursue goals and activities in line with one’s overarching life direction, predicted better academic success across several years of university. Students (n = 769) at a large, U.S. public university were asked to complete a baseline survey in the summer prior to entering university, which included measures for a sense of purpose and background characteristics. Students were then followed throughout their first three years of university. Results demonstrated that higher levels of purpose were associated with a higher grade point average (GPA), more credits earned, less credits dropped, and an increased odds of persisting through the first three years of university. A sense of purpose also appeared to buffer the negative effect of low entrance scores on university GPA. These findings support cultivating a strong sense of purpose prior to entering university as an effective means of improving a variety of academic outcomes.